PROMOTING STUDENTS’ AGENTIC ENGAGEMENT THROUGH PROJECT-BASED LEARNING: CHALLENGES AND SOLUTIONS IN EFL CLASSROOM - Muh. Fakhrul Armas; Maemuna Muhayyang (Universitas Wiralodra, 2026)
Recent studies show that agentic engagement in Project-Based Learning (PjBL) is still not widely understood, particularly in collectivist settings like Indonesia. Much of the existing research has focused on measuring agency or linking it to other factors, but less attention has been given to how agency actually develops and unfolds in everyday classroom interactions. This study seeks to address that gap by examining how students engage in an English as a Foreign Language (EFL) class at Madrasah Aliyah Negeri (MAN) 1 Soppeng, South Sulawesi. Through interviews with 15 students and one teacher, several challenges emerged: language barriers, fear of making mistakes, and limited classroom time often hinder students’ ability to take initiative. The findings also highlight the importance of teacher responses, which can either encourage or discourage students from actively participating. To strengthen agentic engagement, the study suggests adopting creative teaching strategies, building supportive teacher-student relationships, and connecting lessons to students’ real-life goals. These insights not only deepen our understanding of agency in collectivist cultures but also emphasize the need for more research in secondary schools. Ultimately, the study calls for continued exploration to better support student autonomy and empower learners in their educational journey.